SWEET transporters of Medicago lupulina in the arbuscular-mycorrhizal system in the presence of medium level of available phosphorus - A. A. Kryukov; A. O. Gorbunova; T. R. Kudriashova; O. B. Ivanchenko; M. F. Shishova; A. P. Yurkov (Вавиловский журнал генетики и селекции)
Arbuscular mycorrhiza (AM) fungi receive photosynthetic products and sugars from plants in exchange for contributing to the uptake of minerals, especially phosphorus, from the soil. The identification of genes controlling AM symbiotic efficiency may have practical application in the creation of highly productive plant-microbe systems. The aim of our work was to evaluate the expression levels of SWEET sugar transporter genes, the only family in which sugar transporters specific to AM symbiosis can be detected. We have selected a unique “host plant–AM fungus” model system with high response to mycorrhization under medium phosphorus level. This includes a plant line which is highly responsive to inoculation by AM fungi, an ecologically obligate mycotrophic line MlS-1 from black medick (Medicago lupulina) and the AM fungus Rhizophagus irregularis strain RCAM00320, which has a high efficiency in a number of plant species. Using the selected model system, differences in the expression levels of 11 genes encoding SWEET transporters in the roots of the host plant were evaluated during the development of or in the absence of symbiosis of M. lupulina with R. irregularis at various stages of the host plant development in the presence of medium level of phosphorus available for plant nutrition in the substrate. At most stages of host plant development, mycorrhizal plants had higher expression levels of MlSWEET1b, MlSWEET3c, MlSWEET12 and MlSWEET13 compared to AM-less controls. Also, increased expression relative to control during mycorrhization was observed for MlSWEET11 at 2nd and 3rd leaf development stages, for MlSWEET15c at stemming (stooling) stage, for MlSWEET1a at 2nd leaf development, stemming and lateral branching stages. The MlSWEET1b gene can be confidently considered a good marker with specific expression for effective development of AM symbiosis between M. lupulina and R. irregularis in the presence of medium level of phosphorus available to plants in the substrate.